KINETICS OF SELECTIVE CATALYTIC REDUCTION OF NITRIC OXIDE OVER Pt-Cu-ZSM5 CATALYST - Mohd Saaid, Ismail (International Islamic University Malaysia, 2003)
Abstract: Kinetics for the selective catalytic reduction (SCR) of nitric oxide (NO) using i-C4H10 as the reducing agent over Pt-Cu-ZSM5 has been investigated in the temperature range of 200 – 450 oC. Langmuir-Hinshelwood-Hougen-Watson model was proposed for kinetics of the reaction and reaction parameters were evaluated. The heat of adsorption of NO was found to be considerably high, attributed to strong covalent bond between NO gas molecules and metal active sites. Using reaction parameters obtained from the experiment, the heterogeneous model could form a good correlation between experimental and simulated values of NO reduction.